Detection and association of β-lactam resistance genes in Fusobacterium nucleatum and Prevotella intermedia. Investigation of cfxA in saliva samples - Knedahl, Ingeborg; Jakobsen, Sofie (UiT Norges arktiske universitet, 2017)
Abstract Background: Antibiotic resistance is an ever-increasing problem worldwide, caused by unnecessary and excess use of antibiotics. The problem has engaged more attention and research the recent years. Aims: The aim of this study is to detect levels of the antimicrobial resistant gene cfxA in saliva samples, and to investigate the linkage between this gene and the two chosen bacteria; Prevotella intermedia and Fusobactierium nucleatum. The saliva is collected from experienced dentists and dental hygienists, to investigate the presence of the cfxA gene compared to inexperienced 1st and 5th year dental students. Material and method: Saliva was collected from a total of 20 experienced dentists/ dental hygienists at “Universitetstannklinikken” (UTK) and “Tannhelsetjenestens kompetansesenter for Nord-Norge” (TkNN). DNA was extracted, followed by amplification and quantification of the cfxA gene using ddPCR. In addition to saliva collection, a questionnaire was used to report the demographic data, attitudes and hygiene practices in order to study any correlation between levels of the cfxA gene and personal characteristics, e.g. habits, knowledge and commitment to hygiene procedures in the clinic. Results: We detected the resistance gene cfxA in all the participants, but could not detect any significant linkage between the cfxA gene and the two bacteria, P. intermedia and F. nucleatum. The results report no significant difference level of the cfxA gene between the experienced group and previously reported results from dental students. In addition, no positive correlation was found between the level of the cfxA gene and previous use of antibiotics. Conclusion: The study reports higher median values of the cfxA gene in the experienced participants compared to dental students. Also, a higher percentage of the experienced participants had high levels of the cfxA gene compared to dental students. The small sample size in this study is a possible reason for the lack of statistical significance, and it would be ...